KEPRIBADIAN, MOTIVASI, DAN PERILAKU KOMPLAIN BERDASARKAN SUKU - Wandani, Dwi; Simanjuntak, Megawati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2019)
The behavior of complaints is an important issue so that consumers can express their dissatisfaction to the consumption of goods and/or services. This study aims to analyze personality and motivation on complaint behavior based on ethnicity. The design of this study used quantitative and cross-sectional studies with online survey methods. Respondents were selected by purposive sampling techniques and involved 286 college students as participants. Data analysis used the SEMmethod through Analysis of Moment Structures (AMOS) and Smart Partial Least Square (PLS) programs and one way ANOVA difference tests. The result respondents from the three ethnic groups namely Javanese, Batak, and Bugis describe the extrovert personality is the highest proportion of personality amongs three tribes, the highest proportion of respondents among three tribes is moderate category of motivation. However, the result also revealed that the complaint behavior from respondents among three tribes is categorized as low. The results showed that there were significant differences between Javanese and Bataknese in carrying out complaints. Based on the influence test using the SEM, there is a significant influence of personality on the complaint behavior of the Bugis ethnic and there is a significant influence of motivation on complaint behavior on the Javanese.